Optimization of espresso coffee extraction through variation of particle sizes, perforated disk height and filter basket aimed at lowering the amount of ground coffee used. (1st June 2020) - Khamitova, Gulzhan; Angeloni, Simone; Borsetta, Germana; Xiao, Jianbo; Maggi, Filippo; Sagratini, Gianni; Vittori, Sauro; Caprioli, Giovanni
Highlights: Espresso coffee (EC) extraction at various particle sizes has been studied. EC extraction process at constant variables were conducted. Filter baskets and various heights of perforated disc influenced EC extraction. Reduction the amount of ground coffee during the extraction process was implemented. The increase of bioactive compounds had occurred at finer particle sizes. Abstract: Espresso machines maintain constant the extraction process of espresso coffee (EC), however, it is difficult to grind roasted coffee in homogeneous way. This research aims to investigate grinded beans at specific particle sizes in three variously designed filter baskets and to compare the concentration of bioactive compounds while decreasing the amount of ground coffee. Analyses on caffeine, trigonelline and chlorogenic acids are carried out with HPLC-VWD, while volatiles with HS-SPME/GC–MS. Extracting with smaller particles escalates the quantity of bioactive compounds. The amount of caffeine/cup increased moving from 500–1000 µm to 200–300 µm particle size, both in Arabica and Robusta for all filter baskets. Keeping constant the volume of EC at various heights of perforated disc, the amount of bioactive compounds at 12 g were only around 9% lower than at 14 g. The outcomes will support further studies on different extraction processes, to develop more sustainable and economically affordable coffee.